PENGARUH ANALISIS INTERNAL DAN EKSTERNAL TERHADAP KINERJA USAHA KECIL MENENGAH - Novie Wijaya; Meilya Suzan Triyastuti; Rafi Ohorella; Retno Dwi Jayanti (Universitas Nias Raya, 2025)
Budo Village, as one of the coastal areas, possesses considerable economic potential, particularly through the activities of Small and Medium Enterprises (SMEs) managed by the local community. Various types of businesses have developed in this village, ranging from fisheries and marine product processing to service and trade sectors. The growth of SMEs in Budo Village is influenced by both internal and external environmental factors, which help shape the direction and quality of local economic development. This study aims to analyze the influence of internal and external environmental factors on competitive advantage and business performance within the community. The research employs a quantitative approach with data collection techniques using questionnaires distributed to 100 respondents who are SME actors. Data analysis was conducted using validity tests, reliability tests, t-tests, and F-tests. The results show that all variables studied internal environmental factors, external environmental factors, and competitive advantage are proven to be both valid and reliable. Furthermore, these three variables have a positive and significant influence on improving business performance. These findings indicate that strengthening both internal and external supporting factors is crucial to enhancing competitiveness and fostering the growth of SMEs in coastal regions such as Budo Village.